The effect of exclusive breastfeeding on fine motor skills in infants aged 7-12 months in the kapasa health center work area - Muldaniyah, Muldaniyah (Innovative Approaches in Health Science Journal, 2025)
Background: The development phase is an important period for a baby's life. One of the most important factors in the development phase is nutritional needs. Nutrition is needed from when the baby is in the womb until birth. The baby's nutritional needs during pregnancy are obtained from the mother during pregnancy, while nutrition when the baby is born is obtained from exclusive breastfeeding. The purpose of this study was to determine the relationship between exclusive breastfeeding and fine motor skills in infants aged 7-12 months in the Kapasa Health Center work area. Method: This study uses a quantitative research type using a retrospective research design. The sampling technique uses Purposive Sampling. The number of samples is 30 respondents. Analysis using the Chi-square test. Results: The results of the Chi-square test obtained a value of p = 0.004 (p> 0.05) this identifies Ha as accepted, which means there is a relationship between exclusive breastfeeding and fine motor skills in infants aged 7-12 months in the Kapasa Health Center work area. Conclusion: Exclusive breastfeeding plays an important role in supporting the development of infants' fine motor skills. This study recommends that mothers exclusively breastfeed for the first six months of a baby's life and avoid giving complementary foods or formula milk before the age of six months to ensure optimal growth and development of the baby.